Deskripsi Kemampuan Pemahaman Konsep Turunan Berdasarkan Teori APOS pada Siswa Kelas XII SMA - Dwi Fitriani Rosali; Talib; Asdar (Issues in Mathematics Education (IMED), 2019)
This research aims to describe the ability in understanding derivative concepts based on APOS theory. This research was a qualitative descriptive with the subjects were 6 students from class XII MIA at one of Senior High School in Makassar in 2018/2019 academic year which selected for certain purposes, namely students score and teacher recommendations. The instruments used in this research were a test of students' mathematics ability, test in understanding the derivative concepts based on APOS theory, and interviews. The results of the research showed that: (1) the students who have the high ability have fulfilled the indicators of understanding concept at the stage of action, and they fulfilled all indicators of understanding concepts in process and object stages. However, at the schema stage, the students only met 1 indicator of understanding the concept; (2) students who have the average ability have fulfilled the indicators of understanding concept at the action phase, and they fulfilled 1 indicator of understanding concept in the process phase, also they met all the indicators of understanding concepts in the object phase. However, at the schema phase, the students did not meet 1 indicator of understanding concepts; (3) students who have the low ability have fulfilled the indicators of understanding concept at the stage of action, and they fulfilled all indicators of understanding concepts at the process stage. However, the students did not meet the indicator of understanding concepts at the object and schema stage.